Knowledge, attitude and practice study on cardiopulmonary resuscitation among medical and nursing interns - Mendhe, Harshal Gajanan; Burra, Lavanya; Singh, Daneshwar; Narni, Hanumanth (International Journal Of Community Medicine And Public Health, 2017)
Background: Cardiac arrest is a substantial public health problem estimated to account for 15–20% of all death. It is documented that a timely performed cardiopulmonary resuscitation (CPR) can largely prevent sudden death. Being important members of the health care delivery team, medical professionals and nursing staff are deemed to pass the basic skills and expertise which are needed to perform CPR. The principle objectives of the research project are to assess knowledge and attitude of CPR and to compare knowledge regarding CPR among medical and nursing students. Methods: It was a cross sectional study for duration of 2 month from March 2013 to April 2013, conducted among 100 nursing and medical interns of a tertiary care institute in Vijayawada (A.P). Pre tested structured questionnaire of 2010 American health association guidelines for CPR and basic life support (BLS) Practice Test of National Health Care Provider Solutions of 30 questions were used to assess the knowledge, attitude and practice among study participants. Results: The median for knowledge score of MBBS interns was 6 with inter-quartile range 2 and the median for the knowledge score of nursing interns was 6 with inter-quartile range 1. The median for the practice score for MBBS interns was 5 with inter-quartile range of 2.25 and median for practice score in case of nursing interns was 4 with inter-quartile range 2. 36% of MBBS interns had poor knowledge score and 46% of nursing interns had poor knowledge score. Conclusions: The present study identified the knowledge and practice score of BLS or CPR which is poor in both medical and nursing students, even though they have positive and good attitude towards it. BLS training should be the part of the curriculum to solve this issue.